measure the relationship between imported inflation and foreign trade in the Iraqi economy for long 1990-2015 using model nardl - الكبيسي محمد صالح; مثنى تحسين محمود (Journal of Economics and Administrative Sciences, 2018)
The study aims to discuss the relation between imported inflation and international trade of Iraqi economy for the period (1990-2015) by using annual data. To achieve the study aim, statistical and Econometrics methods are used through NARDL model to explain non-linear relation because it’s a model assigned to measure non-linear relations and as we know most economic relations are non-linear, beside explaining positive and negative effects of imported inflation, and to reach the research aim deductive approach was adopted through using descriptive method to describe and determine phenomenon. Beside the inductive approach by g statistical and standard tools to get the standard model explains the relation between international trade and imported inflation in Iraqi economy in Iraq for the period (1990-2015). The most important conclusion was that the governed exchange price system is the less one that affected by imported inflation and it seems obvious through contribution ratio of imported inflation in local inflation rate despite of the big depending of Iraqi economy on world. The most imported recommendation is using multiple exchange prices systems to support necessary goods and services or those can’t be provided by Iraqi economy at this time, conversely this system is been used to prevent some goods and services that are exist locally or harms society.